The Trend of English as Medium of Instruction in Higher Education: A Systematic Literature Review - Sumarni; Sultan Baa; Iskandar Sulaiman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
English as a Medium of Instruction (EMI) has expanded rapidly across non-Anglophone universities over the past two decades, yet the research landscape remains theoretically fragmented and methodologically uneven. This systematic literature review (SLR) synthesises empirical and conceptual scholarship on EMI in higher education published between 2013 and 2024. Following PRISMA 2020 guidelines (Page et al., 2021), a structured search across Scopus, Web of Science, ERIC, and Google Scholar yielded 68 peer-reviewed articles after rigorous screening (initial pool: n = 1,847). Thematic synthesis and bibliometric mapping were applied to the final corpus. Five overarching themes were identified: (1) pedagogical challenges and faculty experience; (2) language attitudes and student outcomes; (3) EMI policy implementation gaps; (4) content learning outcomes; and (5) identity, ideology, and power. A clear temporal pattern was observed: pre-2018 studies relied predominantly on perception-based surveys, whereas post-2018 scholarship has shifted toward qualitative, theoretically grounded, and critically oriented designs. The review proposes the EMI Quality Ecosystem (EQE) model — an original integrative framework linking macro-level policy, meso-level institutional governance, and micro-level classroom dynamics. Findings carry implications for EMI policymakers, curriculum designers, teacher educators, and researchers, particularly regarding the need for discipline-specific support structures and linguistically responsive assessment.